The influence of teaching and learning approaches on student perceptions : HRM perspectives - Tan, Jia Lee (2025)
This study aims to analyze the different learning approaches and the impact on the perception from the tertiary education students which is from the School of Business and Social Science form the private university located in Alor Setar, Kedah. The literature review has shown that the different learning approaches which are the classroom learning, online learning and blended learning are impact to student perceptions, providing different view on the student perception. The research had adopted quantitative approaches with population of the student undergoing their third-level education at private university Alor Setar Kedah. The questionnaire was created and distributed to the third-level education which are the student under their degree level under School of Business and Social Science at private university Alor Setar, Kedah and a total of 152 responses collected. The data collected had been analyze using the SPSS software V29.0 to examine the relationship between different teaching and learning approaches and the impact of each teaching and learning approach towards student perception. The results shows that the diverse teaching and learning approaches had a moderate to high positively impact to the student perception. The Blended teaching and learning approach was showing highest impact towards the student perception while the classroom teaching and learning approach and online teaching and learning approach had moderately impacting the student perception positively. There are also significant differences between different teaching and learning approach to the student perception. These findings believed was contributing to the formation on the future training strategies of the organization when absorbing the new generation to the workplace to ensure innovative outcome, motivate engagement and the efficacy learning approaches implemented